2015
DOI: 10.1515/geoca-2015-0019
|View full text |Cite
|
Sign up to set email alerts
|

Last occurrence of Abathomphalus mayaroensis (Bolli) foraminiferid index of the Cretaceous–Paleogene boundary: the calcareous nannofossil proof

Abstract: Abstract:In the Gaj section (Polish Carpathians, Skole Nappe, Ropianka Formation), the Late Maastrichtian calcareous nannofossil biostratigraphy is compared with foraminiferal zonation based on the occurrence of the planktonic foraminiferid index species Abathomphalus mayaroensis. It appears that the LO of A. mayaroensis, which has been used previously in the studied section as the possible K/Pg boundary indicator is located below the boundary. The disappearance of A. mayaroensis along with other planktonic fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 62 publications
0
4
0
Order By: Relevance
“…Its occurrence depends locally on environmental stress that can exclude this fragile species from the foraminifera assemblage (see Keller and Abramovich, 2009). Therefore, the disappearance of A. mayaroensis cannot be a reliable indicator of age, but rather evidence of environmental change (see also Kędzierski et al, 2015). Similarly, for instance, the nannoplankton species M. murus, index fossil of UC20b TP Zone, also is known as a low-latitude, warm surface taxon, migrating from low-to-high latitudes in accordance with Maastrichtian climate changes .…”
Section: K-pg Boundarymentioning
confidence: 99%
“…Its occurrence depends locally on environmental stress that can exclude this fragile species from the foraminifera assemblage (see Keller and Abramovich, 2009). Therefore, the disappearance of A. mayaroensis cannot be a reliable indicator of age, but rather evidence of environmental change (see also Kędzierski et al, 2015). Similarly, for instance, the nannoplankton species M. murus, index fossil of UC20b TP Zone, also is known as a low-latitude, warm surface taxon, migrating from low-to-high latitudes in accordance with Maastrichtian climate changes .…”
Section: K-pg Boundarymentioning
confidence: 99%
“…Although there could be several reasons for this dearth of youngest Cretaceous planktonic, the most likely one, consistent with the sedimentological observations, is that being a hiatus at the peak of the Cretaceous regression. The most plausible explanation of the absence of index taxa Abathomphalus mayaroensis is the bathymetry, because this species is bathypelagic, thus absent in shallower areas of the basin (Farouk, 2014;Kędzierski et al, 2015). Another argument is the fact that A. mayaroensis is seldom found in tropical areas (Premoli- Silva and Verga, 2004;Abdallah and Obaidalla, 2013).…”
Section: Interpretations Planktonic Foraminiferal Biostratigraphymentioning
confidence: 99%
“…Notable considerations on the differences in chronostratigraphic position of a certain zonal species of planktonic foraminifera were given in the paper Kędzierski et al (2015). Emphasizing that far more precise bio strati graphic data could be obtained by integrating the results of a number of different methods, such as palaeomagnetostratigraphy and biostratigraphy based on different fossil groups, the authors indicated the existance of the problem of diachronicity of the first and the last occurrence of zonal species, caused by palaeoenvironmental conditions in different bioprovinces.…”
Section: Biostratigraphical Commentsmentioning
confidence: 99%